Analysis Marketing Strategi On Pizza Ala Ambu - Henriawan, Desan; Lestari, Bunga Sri; Jannah, Ratu Nadia Raudhotul; Ashari, Suji Bil (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
The purpose of this study is to examine in depth the marketing strategies implemented by “Pizza Ala Ambu,” a growing home-based culinary business specializing in affordable homemade pizza. The analysis focuses on how the business formulates and applies segmentation, targeting, and positioning (STP) to identify and reach its potential market effectively. Furthermore, this study explores the marketing mix strategy (product, price, place, and promotion) developed to enhance customer value and strengthen the competitive position of Pizza Ala Ambu amid the increasing competition within the local food industry. Using a descriptive qualitative method, data were collected through interviews with the business owner, direct observation of the production and selling processes, and documentation related to marketing activities. The findings reveal that Pizza Ala Ambu is able to attract consumer interest through the uniqueness of its product, the use of fresh ingredients, and pricing strategies that align with the purchasing power of its target market. Promotion through digital platforms particularly social media also plays a significant role in increasing brand awareness and customer engagement. Overall, the study concludes that the marketing strategies implemented by Pizza Ala Ambu are effective in supporting business growth, increasing sales performance, and building a strong brand identity as a provider of homemade pizza that is both high-quality and affordable. The study also highlights several challenges faced by the business and provides recommendations for future development.